2021
DOI: 10.1155/2021/4745853
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Percutaneous Kyphoplasty with or without Pedicle Screw Fixation in Osteoporotic Thoracolumbar Vertebral Fractures: A Retrospective Study

Abstract: Background. Osteoporotic thoracolumbar compression fractures have become a great social burden due to the aging tendency of population. This study is aimed at comparing the clinical and radiological outcomes of percutaneous kyphoplasty with or without pedicle screw fixation in patients with osteoporotic thoracolumbar fractures. Hypothesis. There is a difference in clinical outcomes between percutaneous kyphoplasty with pedicle screw fixation and percutaneous kyphoplasty. Methods. This retrospective study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…There have been some reports that secondary vertebral fractures after PVP or PKP, including further compression of previously treated vertebrae and new fractures in adjacent vertebrae (11,16,49,50). Kim and Rhyu (49) showed that the incidence of fractured vertebrae recollapse was 12.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been some reports that secondary vertebral fractures after PVP or PKP, including further compression of previously treated vertebrae and new fractures in adjacent vertebrae (11,16,49,50). Kim and Rhyu (49) showed that the incidence of fractured vertebrae recollapse was 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In the PKP group of this study, 10 (12.82%) of 78 patients had complications, including cement leakage (n = 3), fractured vertebrae recollapse (n = 2) and adjacent vertebral fracture (n = 5), these incidences are slightly lower than the abovementioned studies. In addition, Huang et al (16) reported that 23 patients with osteoporotic thoracolumbar fractures (48.9%) in PKP group had complications, including cement leakage (n = 10), fractured vertebrae recollapse (n = 12) and reoperation due to refractures (n = 2), and the complications in PPSF+KP group were significantly less (p < 0.05), including cement leakage (n = 2), wound infection (n = 1), and recollapse at the final follow-up (n = 2). In this study, 3 (20.51%) of 24 patients had complications, including cement leakage (n = 1), fractured vertebrae recollapse (n = 1) and adjacent segment fracture (n = 1), and there was no significant difference in the incidence of each complication between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the higher frequency complication of osteoporosis, osteoporotic vertebral compression fractures (OVCF) are the most common clinical fracture, and there are nearly 1.4 million new cases per year. 1 Epidemiology shows that the thoracolumbar vertebral body is the most common site for osteoporotic fractures, and the incidence of thoracolumbar OVCF accounts for 53% of all fragility fractures. 2 It can cause severe and long-term low back pain, even disability, and seriously affect the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various minimally invasive techniques have developed rapidly. Currently, minimally invasive pedicle screw internal fixation is used to restore the height of the compressed vertebral body in patients, which can make up for the insufficiency of traditional treatment and surgery [ 6 ]. In this study, we chose open and minimally invasive internal fixation with an arch nail to analyze the effect on the stress response of patients with vertebral fractures, hoping to improve the function of the lumbar spine and improve their ability to live, respectively, as reported below.…”
Section: Introductionmentioning
confidence: 99%